1985
DOI: 10.1021/j100256a025
|View full text |Cite
|
Sign up to set email alerts
|

Charge separation in photoinitiated electron-transfer systems with polyviologen polyelectrolytes as quenchers

Abstract: 1937rings, respectively. This suggestion is consistent with the observed Si/Al ratio for ferrierite. The present calculations further indicate that diagonal pairing is favored relative to the meta or ortho pairings in accordance with electrostatic principles and the aluminum avoidance rule.2. As observed in our previous work on mordenite and ZSM-5, the analysis of the formal atomic charges distributions in the clusters indicates the highly covalent nature of aluminosilicate frameworks. The spreading of the neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 2 publications
2
15
0
Order By: Relevance
“…Shielding [Ru(bpy) 3 ] 2+ from water enhances the luminescence quantum yield, 42 since the presence of water increases non-radiative decay. 43 Therefore, localization of the complex in a hydrophobic, water-excluding PSS environment is consistent with the observed increase in emission intensity and lifetime, as well as with the red-shifts of both MLCT absorption and emission maxima. In parallel studies, we have observed that [Ru(phen) 2 dppz] 2+ emission is ''turned on'' when bound to PSS, to almost the same extent as when bound to singlestranded polynucleotide [poly(dA)] at low ionic strength (ESI, Fig.…”
Section: The Effect Of Pss On the Absorption And Emission Spectra Of ...supporting
confidence: 84%
“…Shielding [Ru(bpy) 3 ] 2+ from water enhances the luminescence quantum yield, 42 since the presence of water increases non-radiative decay. 43 Therefore, localization of the complex in a hydrophobic, water-excluding PSS environment is consistent with the observed increase in emission intensity and lifetime, as well as with the red-shifts of both MLCT absorption and emission maxima. In parallel studies, we have observed that [Ru(phen) 2 dppz] 2+ emission is ''turned on'' when bound to PSS, to almost the same extent as when bound to singlestranded polynucleotide [poly(dA)] at low ionic strength (ESI, Fig.…”
Section: The Effect Of Pss On the Absorption And Emission Spectra Of ...supporting
confidence: 84%
“…Firstly, the gel environment strongly contributes to the decrease of the mobility of [Ru(bpy) 3 ] 2+ . 58 Shielding [Ru(bpy) 3 ] 2+ from water should therefore also promote lifetime enhancement. 57 They established a correlation between the lifetime and fluorescence anisotropy, and showed that the cross-linked environment restricted the probe mobility.…”
Section: (4) Photoluminescence Lifetime and Quantum Yield Studiesmentioning
confidence: 99%
“…Polyviologens first attracted attention when Sassoon et al reported the participation of various polyviologen derivatives in photoinitiated electron-transfer reactions through quenching photoluminescent ruthenium complexes. 17 The quenching behavior confirms that polyviologens rapidly accept excitedstate electrons. This was further evidenced by the later observation that photoexcited CdSe quantum dots transfer electrons to poly(p-xylylviologen) when two materials are prepared into composite solid-state films.…”
Section: ■ Introductionmentioning
confidence: 70%
“…Polyviologens, first reported in 1971, are a unique class of organic polycationic polymers, with alternating copolymer structure featuring a viologen ( N , N -disubstituted-4,4-bipyridinium dication) and a variable linker group connecting the viologen groups . Aliphatic and unsaturated hydrocarbons of various carbon chain length (e.g., 3–11), as well as aromatic linker groups, have been synthesized and characterized previously. A generalized polyviologen structure is presented in Figure , along with the structure of a commonly cited polyviologen derivative, poly­( p -xylylviologen). Although most commonly reported redox polymers involve multistep synthetic routes, polyviologens can be easily synthesized from low-cost precursors in a single step.…”
Section: Introductionmentioning
confidence: 99%